THE INFLUENCE OF TEACHING STYLE AND MOTOR SKILLS ON THE BOTTOM PASSING LEARNING OUTCOMES IN THE VOLLEYBALL - Ahmad Muchlisin Natas Pasaribu (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
The purpose of this research is to find the effectiveness of teaching style to the learning outcomes of passing motor skills under the volleyball. The Method is Used by experiment with 2 x 3 factorial design. This research is Implemented at SMPN 3 Satu Atap Labura with sample of class VIII. The Results of This study concluded that: (1) There are no differences between the forces Teaching reciprocity and training on the learning outcomes of passing down in a manner Overall (2) there are differences between reciprocal teaching style and inclusion To the overall passing learning outcome (3) There are differences Between teaching practice style and inclusion to lower passing learning outcomes Overall. (4) There are interaction between teaching styles (reciprocal, training, And inclusion) and motor skills (high and low) on learning outcomes Passing down as a whole. (5) There are differences teaching styles Reciprocal and training on lower passing learning outcomes in students High motor skills. (6) There are a differences in reciprocal teaching style and Inclusion of lower passing learning outcomes in students with motor skills High. (7) There are different styles of practice teaching and inclusion to results Learn passing down on high skill motor students. (8) There are Differences in reciprocal teaching styles and training on passing learning outcomes (9) There are a differences in teaching styles reciprocity and inclusion to lower passing learning outcomes in students Low motor skills. (10) There are different teaching styles and practice Inclusion of lower passing learning outcomes in students with motor skills lowKeywords: Teaching Styles, Motor Skills, The result of passing down learning